Brain anatomy of symptom stratification in schizophrenia: a voxel-based morphometry study. (4th July 2017) - Delvecchio, Giuseppe; Lorandi, Alessandra; Perlini, Cinzia; Barillari, Marco; Ruggeri, Mirella; Altamura, A. Carlo; Bellani, Marcella; Brambilla, Paolo
Abstract: Background: Although some Magnetic Resonance Imaging (MRI) studies have investigated the relationship between clinical severity and neuroanatomical alterations in patients with schizophrenia (SCZ), the biological signature associated with illness severity in schizophrenia is still uncertain. Therefore, this study aims to investigate structural brain abnormalities in SCZ, with particular regards to the identification of potential deficits associated with the severity of illness. Methods: In total, 1.5T MRI data were acquired for 61 subjects with SCZ and 59 matched healthy controls (HC). The patient group was divided in two sub-groups based on clinical severity, one composed of 34 mild-to-moderately ill patients, and the other of 27 severely ill patients, and compared with matched HC. Results: The whole group of patients with SCZ had significantly reduced grey matter (GM) volumes in the left inferior and middle temporal gyrus compared to HC ( p  < 0.05, pFWE corrected). Furthermore, compared to HC, patients with mild-to-moderate illness showed decreased GM volumes in the inferior and middle temporal gyrus, whereas those with severe illness had reduced GM volumes in the middle temporal gyrus and cerebellum bilaterally (all p  < 0.001 uncorrected). No differences were observed between the two sub-groups of patients. Conclusion: The results showed significant GM volume reductions in temporal regions in patients with SCZ compared to matched HC, confirming the role of these regions in the pathophysiology of SCZ. Furthermore, specific cerebellar grey matter volume reductions were identified in patients with severe illness, which may contribute to stratifying patients with SCZ according to their clinical phenotype expression, ultimately helping in guiding targeted therapeutic/rehabilitation interventions.